Administração rural e extensão rural - Abreu Neto, Francisco Antônio de (1982)
The present research investigates the formulation of country (rural) management that the Rural Extension suggests to the agricultural activity. The basic hypothesis which directed the research was: The rural administration is 'a by-product of the capitalist way of production embraced into the present historic period of its evolution. The empirical material was constituted by the official documents of ACAR and further by EMATER, MG, which contains the administrative directions for the enterprises and the rural region. The theoretical standard, support of the analysis of the empirical material is constituted of a part in which one characterizes the way of capitalist production of its historical origin to the present stage of its evolution. In a second stage one developed the study of the historical origins of the scientific management, and the various transformations which the theory of administration went through. In a third stage it was discursed the proposal of the rural management for a period of transition: integration of the functions of productor and manager into productor rural administrator. The analysis of the empirical material has proved that the evolution of the proposals of formulation on rural management followed the transformation of the way of production in the agriculture with the predominance of the capitalist production, even through inequal and combined.